Religious-Magic Beliefs of the Sasak Community in East Lombok-NTB - Lalu Murdi (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
This study presents another uniqueness of the Sasak people of Lombok, NTB, especially with regard to the picture of religious-magical beliefs that are still attached to this day. One of the aims of this research is to provide an overview of the variety of Indonesian culture that differs from region to region. The research approach used in this study is a qualitative approach with ethnographic methods. The results showed that in the Sasak community in particular and in Jerowaru District in particular, the spatial aspect of this study showed that the community still had magical religious beliefs which were believed in almost all areas of life, starting from farming, when building buildings, determining good days and so on.